DINAMIKA SENTRALISASI DAN DESENTRALISASI DI INDONESIA Konfigurasi Baru Hubungan Pusat Daerah Pasca Penguatan Status Provinsi Sebagai Daerah Otonom - Rira Nuradhawati; Muhammad Aldi Rahmandika (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
The transformation of regional autonomy architecture in post-reform Indonesia reached a crucial point with the enactment of Law No. 23 of 2014 concerning Regional Government, which repositioned provinces as autonomous regions and extensions of the central government. This paper analyzes this change as a dualistic policy response: a structural correction to the dysfunction of decentralization following Law No. 22/1999, as well as a soft recentralization strategy. Building on the framework of rescaling governance and multilevel governance, the analysis is conducted through policy and institutional analysis of relevant legal documents, regulations, and academic literature. The results show that Law No. 23/2014 reconfigures the central-regional relationship into a recentralization through rescaling model, characterized by three findings: (1) a hybrid institutional structure in which provinces play a dual role as autonomous regions and representatives of the central government; (2) soft recentralization mechanisms through NSPK, DAK, and centralized information systems that in practice limit the policy space of districts/cities in determining spending priorities and public service standards; (3) the governance paradox of strengthening vertical coordination on the one hand, but weakening local innovation due to the standardization of regional programs and the complexity of accountability on the other. The study's conclusions indicate that central government control has not been reduced, but rather re-institutionalized by strengthening the position of provinces as mediators, creating a layered power structure that presents new challenges to the effectiveness of regional autonomy and public accountability.